Quantitative analysis of afferents expressing substance P, calcitonin gene‐related peptide, isolectin B4, neurofilament 200, and Peripherin in the sensory root of the rat trigeminal ganglion. Issue 1 (1st January 2015) - Bae, Jin Young; Kim, Jae Hyun; Cho, Yi Sul; Mah, Won; Bae, Yong Chul
ABSTRACT Substance P (SP), calcitonin gene‐related peptide (CGRP), and isolectin B4 (IB4) are widely used as markers for peripheral neurons with unmyelinated fibers, whereas neurofilament 200 (NF200), and Peripherin are used as markers for neurons with myelinated fibers, and with unmyelinated or small‐caliber fibers, respectively. To study the selectivity of these markers for specific neuronal types, we analyzed their expression in neurons in the rat trigeminal ganglion by light‐ and electron‐microscopic immunocytochemistry. Most SP‐immunopositive (+), CGRP+, and IB4+ fibers were unmyelinated, but a small fraction (∼5%) were small myelinated fibers (<20 µm2 in cross‐sectional area, equivalent to <5 µm in diameter, Aδ fiber). Similarly, whereas the majority of NF200+ fibers were myelinated, a large fraction (23.9%) were unmyelinated, and whereas the majority of Peripherin+ fibers were unmyelinated and small myelinated, a significant fraction (15.5%) were large myelinated (>20 µm2 in cross‐sectional area, equivalent to >5 µm in diameter, Aβ fiber). Our findings confirm that SP, CGRP, and IB4 can be used as reliable markers for neurons with unmyelinated fibers, and question the suitability of NF200 as a marker for neurons with myelinated fibers, and of Peripherin as a marker for neurons with unmyelinated, or fine‐caliber fibers. J. Comp. Neurol. 523:126–138, 2015. © 2014 Wiley Periodicals, Inc.